Євстахій Струк як учасник національно-визвольного руху в першій половині ХХ ст. - Мельник, Роман; Мельник, Віра; Melnyk, Roman; Melnyk, Vira (Видавництво Львівської політехніки, 2020)
Стаття присвячена проблемі збереження історичної пам’яті та дослідження розвитку національно-патріо- тичного руху в Галичині на початку XX ст. У статті проаналізовано життя та діяльність Євстахія Струка у період 1909–1941 рр., показано його роль у національно-визвольному русі українців у першій половині XX ст.

The article is devoted to the problem of preserving the historical memory and exploring the development of the national-patriotic movement in Galicia in the early XX century. The first days of the establishment of Soviet power in Ukraine in the first half. Twentieth century. characterized by the beginning of political repression of the region. Terror was at once intentional and organized. At the sight of Soviet power, virtually all sections of the Ukrainian nation, namely the intelligentsia, the military, politicians, doctors, church and cultural figures, as well as the peasantry, appeared. Studying biographical facts about the life and activities of the fighters for the freedom and independence of Ukraine significantly supports patriotism and the national idea. The article analyzes the life and activities of Eustachian Struk in the period 1909–1941, and shows his role in the national liberation movement of Ukrainians in the first half of the XX century. Struk’s activity as an enlightened Ukrainian intellectual, who participated in the formation of Plast, the OUN, traversed the camps, worked hard to develop a national idea. The article also examines activities at the Lviv Medical Institute, from professional responsibilities to maintaining patriotic attitudes among employees and the judiciary. Particular attention is paid to the study of Eustachius in 1941, when he used his official position to act against the Soviet authorities, realizing that the consequence would be loss of work, peace for relatives and even the cost of living. The order freed about forty students of illegally imprisoned medical students who were preparing to be executed by one order. As a result of Eustachius, the force was taken out of the workplace, “dragging the corridors and stairs of the Institute”, and then waiting for him the walls of “Prison on Lons”. Eustachian Struck is questioned, often using torture methods, as evidenced by the loose skin on his back and the numerous bruises. In June 1941, German troops were approaching Lviv, and the Soviet authorities realized that it was necessary to leave positions and to trace the traces of their crimes. At this time, about five thousand political prisoners were being held in the prisons of Lviv, and it was impossible to take them to the East together with the closest surroundings of Soviet power in the Lviv region. One mass shooting was found out. Among those shot was Eustachius Struck. Later, his wife identifies the body and buries it in the Lychakiv Cemetery. And son Danilo will become a professor at the University of Toronto, where he will publish a multi-volume encyclopedic publication about his native Ukraine, which contains an article about his father.
Eustakhy Struk, as a participant of the national liberation movement in the first half of the XX century
Keywords: Євстахій Струк; “Тюрма на Лонського”; Львівський медичний інститут; національно- патріотичний рух; Галичина; Верхнє Синьовидне; Eustachy Struk; “Prison on Lonsky”; Lviv Medical Institute; national-patriotic movement; Halychyna; Verkhnie Synovydne; 94(477); 323.1(092)